Enhanced removal of nitrate and refractory organic pollutants from bio-treated coking wastewater using corncobs as carbon sources and biofilm carriers. (December 2019) - Sun, Guoping; Wan, Junfeng; Sun, Yichen; Li, Haisong; Chang, Chun; Wang, Yan
Abstract: The quality of the bio-treated coking wastewater (BTCW) is difficult to meet increasingly stringent coking wastewater discharge standards and future wastewater recycling needs. In this study, the pre-treatment process of BTCW was installed including the two up-flow fixed-bed bioreactors (UFBRs) which were separately filled with alkali-pretreated or no alkali-pretreated corncobs used as solid carbon sources as well as biofilm carriers. Results showed that this pre-treatment process could significantly improve the biodegradability of BTCW and increase the C/N ratio. Thus, over 90% of residual nitrate in BTCW were removed stably. Furthermore, GC-MS analysis confirmed that the typical refractory organic matters decreased significantly after UFBRs pre-treatment. High-throughput sequencing analysis using 16S rRNA demonstrated that dominant denitrifiers, fermentative bacteria and refractory-organic-pollutants-degrading bacteria co-existed inside the UFBRs system. Compared with no alkali-pretreated corncobs, alkali-pretreated corncobs provided more porous structure and much stable release of carbon to guarantee the growth and the quantity of the functional bacteria such as denitrifiers. This study indicated that the UFBRs filled with alkali-pretreated corncobs could be utilized as an effective alternative for the enhanced treatment of the BTCW. Graphical abstract: Image 1 Highlights: Corncobs can be used as carbon source and biofilm carriers for BTCW pre-treatment. UFBRs with corncobs could improve the biodegradability and C/N ratio of BTCW. Refractory organics and nitrate were synergistically removed in UFBRs. Alkali-pretreated corncobs as ideal carriers enhance the growth of diverse bacteria.